2021
DOI: 10.1038/s41598-021-81897-y
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum analysis of inborn errors of metabolism for expanded newborn screening in a northwestern Chinese population

Abstract: Expanded newborn screening facilitates early identification and intervention of patients with inborn errors of metabolism (IEMs), There is a lack of disease spectrum data for many areas in China. To determine the disease spectrum and genetic characteristics of IEMs in Xi'an city of Shaanxi province in northwest China, 146152 newborns were screening by MSMS from January 2014 to December 2019 and 61 patients were referred to genetic analysis by next generation sequencing (NGS) and validated by Sanger sequencing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 35 publications
3
27
0
1
Order By: Relevance
“…The incidence of GA1 in the selected southern Chinese population was about 1 in 47,044 births, which is comparable to other studied populations [15,16]. Comparing with the incidence reported in different regions of China, the local incidence is higher that reported in Zhejiang province (1:64,708) and Jiangsu province (1:89,335) in southern China [17,18], and Xi'an city (1:73,076) in northern China [19].…”
Section: Discussionsupporting
confidence: 67%
“…The incidence of GA1 in the selected southern Chinese population was about 1 in 47,044 births, which is comparable to other studied populations [15,16]. Comparing with the incidence reported in different regions of China, the local incidence is higher that reported in Zhejiang province (1:64,708) and Jiangsu province (1:89,335) in southern China [17,18], and Xi'an city (1:73,076) in northern China [19].…”
Section: Discussionsupporting
confidence: 67%
“…The incidence of GA1 in the selected southern Chinese population was approximately 1 in 47,044 births, similar to other studied populations [ 13 , 14 ]. Compared with the incidence reported in other Chinese regions, the local incidence is higher than that reported in the Zhejiang (1:64,708) and Jiangsu (1:89,335) provinces of southern China [ 15 , 16 ] and Xi’an City (1:73,076) in northern China [ 17 ].…”
Section: Discussionmentioning
confidence: 76%
“…NBS for PCD has been successfully implemented in most parts of China, patients usually had better prognosis following early L-carnitine therapy. The incidence of PCD varies greatly throughout China, ranging from 1:8,938 to 1:48,717 [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, our data revealed that c.760C>T (p.R254*) was the most common variant in this cohort of patients, and its allele frequency was almost equal to the sum of the other two variants. c.760C>T (p.R254*) is a loss-of-function variant that can cause severe clinical symptoms, it was common in southern China but was rarely detected in northern China[14,22,[24][25][26], indicating this variant presented different geographic distribution. Whereas c.1400C>G (p.S467C) with residual function may result in a milder phenotype, it was common in both southern and northern China[14,22,24, 26], suggesting this variant was common in the general Chinese population.Regarding the relationship between genotype and biochemical phenotype, signi cant difference was observed in C0 levels between patients with N/N and M/M genotypes, and most patients with N/N genotype had low C0 levels compared to the N/M group, indicating patients with null variants were associated with low C0 levels.…”
mentioning
confidence: 99%